IMPLEMENTATION OF EFFECTIVE ANTI-CRISIS MANAGEMENT STRATEGIES OF HIGH-TECH ENTERPRISES IN THE CONDITIONS OF GLOBAL ECONOMIC CHALLENGES - Lebedev, Oleg (Current Problems of Sustainable Development, 2026)
The article explores approaches to the formation and implementation of effective anti-crisis management strategies for high-tech enterprises in the context of modern global economic shocks. The features of crises that arise under the influence of macroeconomic instability, geopolitical factors, disruptions in global supply chains, as well as new technological transformations are considered. Methodological principles for the formation of adaptive elements of the management system that contribute to ensuring the sustainability and competitiveness of enterprises are proposed. Practical recommendations are based on the generalization of world experience and domestic realities. The article considers the mechanism of implementing anti-crisis strategies on the platform of high-tech enterprises. The author proposes an algorithm for forming an effective anti-crisis management strategy, which takes into account the peculiarities of the innovation environment and rapidly changing market conditions. An analysis of the key stages of developing and implementing anti-crisis measures is carried out, which allows increasing the adaptability of enterprises and ensuring the stability of their development in crisis situations. The proposed approach contributes to the optimization of management decisions and strengthening the competitive positions of high-tech companies. High-tech enterprises are a significant engine of innovative economic development and the formation of competitive advantages of countries in the global market. At the same time, they are characterized by increased sensitivity to external and internal risks, especially in the context of global economic challenges, which include cyclical crises, pandemics, changes in the regulatory framework, geopolitical instability and disruptions in supply chains. Therefore, the implementation of effective anti-crisis management strategies is of critical importance for their survival and sustainable development. Crisis management is defined as a system of strategic and tactical measures aimed at identifying, analyzing and neutralizing crisis situations. In the conditions of the high-tech sector, the peculiarity lies in the need to take into account the speed of technological change, the intensity of the innovation process and the complexity of organizational structures as a whole. The methodological basis is a systems approach that considers the enterprise as an open system that interacts with the external environment. The use of scenario forecasting models, risk management, as well as the principles of flexibility and adaptability allows developing comprehensive strategies that are able to respond to changing conditions and transform business models in the shortest possible time.